Oil-water separation phenomenon due to corrosion cavity and scale sediments build-up in horizontal pipeline - Abdullahi, Nuhu (Cranfield University, 2012)
The concurrent flow of two immiscible liquids (Oil-Water) in pipelines is usually encountered in oil production and pipeline transportation. Water is present in crude oil and separation facilities. The aim of this thesis is to investigate the effect of pipe deformations caused by corrosion cavity and scale sediments build-up on the water cut at the pipe wall. An extensive literature review survey on both experimental and numerical investigation has been performed on oil-water flows in horizontal pipelines. Two multiphase flow models (Mixture and Eulerian models) were formulated and presented with the corresponding conservation equations. The three major turbulent modelling approaches to capture turbulent phenomenon were described; Reynolds Averaged Navier-Stokes Equations (RANS) was selected as an appropriate turbulence model for turbulent flow simulations. Preliminary runs were performed for two of the validation cases in order to estimate the pipe entrance length and establish the parameters of the reference state corresponding to pure oil and oil-water. Validation studies were performed to choose the appropriate multiphase model. The results showed that Eulerian multiphase model was fairly more accurate and acceptable in comparison to the mixture model. A further Validation studies was also conducted to select the droplet diameter, whereby appropriate droplet diameter of 3×10-5mm was selected. The corrosion cavity and scale sediments were modelled with rectangular cavity and cubical obstacle respectively oriented perpendicular to the pipe flow. The model geometries and computational mesh were generated with GAMBIT (2.4) and exported to FLUENT (6.3). The simulation was conducted for input water volume fraction of 0.1 and 0.3, Reynolds number of 18,500 and 22,000. Configurations of 16 cases were considered because of computational requirements. Numerical simulation of oil-water pipe flow with corrosion cavity and cubical obstacle were performed and analyses of flow features have been described. Effect of aspect ratio, input water volume fraction and Reynolds number on the amount of water volume fraction at the pipe wall, cavity and around cubical obstacle have been analysed. Quantitative data of maximum and minimum water volume fractions in the pipe, cavity walls and around the cubical obstacle have been computed and compared. The results indicated that around the cavity, turbulence was produced resulting to recirculation, mixing and separation of water from oil. Similarly, oil-water separate from the front, sidewalls and behind the cubical obstacle which lead to formation of different types of vortices. It was observed that water segregated faster with increase in input water fraction and decrease in Reynolds number. However, more water settled to the bottom of deep cavity than shallow cavity and the area of pipe wall wetted by water reduced as the Reynolds number increases. Parametric study on cavity flow has been conducted with the new adjusted turbulent viscosity with damping functions. The results showed improvement on water volume fraction distribution behaviour in pipe and cavity wall surfaces.